(untitled) (Colombia Medica, 1990)
The seroprevalence of antibodies against HIV-1 in prostitutes of Cali, Colombia, was assessed. Related to serology, a was applied to explore patterns of socio-cultural and sexual behavior. A total of 1,066 women were studied. Only 2 (0.18%) positive results were obtained using the western blot technique. Compared to other countries, this seroprevalence is rather low.